2020
DOI: 10.1002/leg3.62
|View full text |Cite
|
Sign up to set email alerts
|

Functional and pasting properties of fortified complementary foods formulated from maize (Zea mays) and African yam bean (Sphenostylis stenocarpa) flours

Abstract: Studies were conducted on the functional, pasting and micronutrient content of complementary weaning foods from maize (Zea mays) and African yam bean (AYB; Sphenostylis stenocarpa). The complementary foods were fortified with cattle bone meal, Brachystegia eurycoma (achi)/potash emulisified with red palm oil and Moringa oleifera, to improve the micronutrient content. Maize and AYB (malted and unmalted) were processed into flours, and the fortificants were subjected to different treatments to ascertain the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The high pasting temperature may be attributed to the higher starch or sugar content. Anosike et al, [ 56 ] reported pasting temperature of 90−92°C which was higher than the present study PT gives an indication of the gelatinization temperature during processing. It is the temperature at which the first detectable increase in viscosity is measured and is an index characterized by initial change due to the swelling of starch.…”
Section: Resultscontrasting
confidence: 73%
“…The high pasting temperature may be attributed to the higher starch or sugar content. Anosike et al, [ 56 ] reported pasting temperature of 90−92°C which was higher than the present study PT gives an indication of the gelatinization temperature during processing. It is the temperature at which the first detectable increase in viscosity is measured and is an index characterized by initial change due to the swelling of starch.…”
Section: Resultscontrasting
confidence: 73%
“…The highest PT of barley flour in comparison to blends indicates the presence of starch and soluble β‐glucan that is highly resistant to swelling and rupturing (Kaushal & Sharma, 2014). Peak time also dropped with increasing chickpea concentration owing to reduced level of association among starch granules (Anosike et al ., 2020). Peak viscosity (PV) decreased as chickpea flour's percentage increased to 40%.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to barley, legumes have relatively high amylose with less swelling and leaching, which could be the reason why blends of chickpea-barley showed a lower Setback Viscosity (Jeong & Chung, 2019). The highest breakdown viscosity (BV) was found in barley flour and declined with increasing chickpea proportion because gelatinized starch got trapped in protein, and improved starch stability (Anosike et al, 2020). According to Tiga et al (2021) higher the SV, syneresis occurs rapidly, which is bad for pasta production because it causes a quick loss of quality.…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…The BDs of five flour samples were not significantly different ( p > 0.05) and significantly lower ( p < 0.05) than the BD of commercial wheat flour ( Table 3 ). Klang et al [ 30 ], Dereje et al [ 58 ], and Anosike et al [ 63 ] have mentioned that flours with BD lower than 1 g/mL can be used in manufacturing low-bulk weaning foods and high-energy foods. In addition, it facilitates easy storage, transport, and marketing due to low volume of packaging material requirement to store the flours [ 58 ].…”
Section: Resultsmentioning
confidence: 99%